2017
DOI: 10.1111/ajco.12828
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socioeconomic factors and distance to radiotherapy on breast‐conserving surgery rates for early breast cancer in regional Australia; implications of change

Abstract: A strong association between distance to radiotherapy and the type of surgery for early breast cancer was found. Improving access to radiotherapy therefore has the potential to improve breast cancer outcomes for women in regional Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This is especially pressing for radiotherapy as the nature of fractionated radiotherapy requires patients to travel to the centres more frequently. For many patients, travel to cancer treatment is described as an inconvenience and a practical hardship [3, 4]. It is not surprising that studies have found that distance plays a major role in acceptance of radiotherapy, whereby its utilisation relies fairly on convenience and proximity to the radiotherapy facilities [59].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially pressing for radiotherapy as the nature of fractionated radiotherapy requires patients to travel to the centres more frequently. For many patients, travel to cancer treatment is described as an inconvenience and a practical hardship [3, 4]. It is not surprising that studies have found that distance plays a major role in acceptance of radiotherapy, whereby its utilisation relies fairly on convenience and proximity to the radiotherapy facilities [59].…”
Section: Introductionmentioning
confidence: 99%
“…29 For rural patients with breast cancer (living > 100 km from radiotherapy), the higher rate of mastectomy is largely influenced by the location of their treatment services, not cancer pathology. 30 Improving MDTs will require both Commonwealth and state government investment to ensure a whole-of-hospital service. There have been successful initiatives, such as the NT Plastic Surgeons Program, where breast cancer services and training can be done locally.…”
Section: Multidisciplinary Teammentioning
confidence: 99%
“… 100 However, regional women who lived ≥100–200 km away (vs <100 km) from a radiotherapy service were twice as likely to have a mastectomy. 101 …”
Section: Patient and Tumour Characteristicsmentioning
confidence: 99%